1936
DOI: 10.1152/ajplegacy.1936.118.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Renal Blood Flow of Unanesthetized Rabbits and Dogs in Diuresis and Antidiuresis

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1937
1937
1958
1958

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The diuretic action of these drugs may be accounted for by a direct renal action (16,17). Diuresis after single doses of mercurial compounds is not associated with an increase in the renal blood flow or in glomerular filtration rate but is apparently the result of a decreased tubular reabsorption of certain electrolytes (18)(19)(20). It is not clear whether the depression of reabsorption occurs in the proximal or in the distal tubule.…”
Section: Discussionmentioning
confidence: 99%
“…The diuretic action of these drugs may be accounted for by a direct renal action (16,17). Diuresis after single doses of mercurial compounds is not associated with an increase in the renal blood flow or in glomerular filtration rate but is apparently the result of a decreased tubular reabsorption of certain electrolytes (18)(19)(20). It is not clear whether the depression of reabsorption occurs in the proximal or in the distal tubule.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout 300 mOsm/L. the entire course of water diuresis, the filtration _____ rate remains essentially unchanged (18)(19)(20). Hormonal and nervous factors, i.e., pituitrin, epinephrine, thyroxine, and painful or emotional stimuli, have profound effects on both the course and amount of the diuresis (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…
It has been shown that the creatinine clearance in man (Blumgart, Gilligan, Levy, Brown, and Volk, 1934) or dogs (Davenport, Fulton, Van Auken and Parsons, 1934;Walker, Schmidt, Elsom, and Johnston, 1937) is not increased by mercurial compounds; nor did thermostromuhr measurements in anaesthetized dogs reveal any constant changes of the renal blood flow when mercurial diuretics were injected (Walker et al, 1937). It was, therefore, concluded that the mercurial compounds exert their diuretic effect by reducing the tubular water reabsorption.
…”
mentioning
confidence: 98%